1997
DOI: 10.1136/adc.76.4.341
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth as predictor of atopic manifestations

Abstract: The relation between month of birth, sensitisation, and manifestations of atopy was assessed in 209 children who were followed from birth to 12-15 years. Children born during the tree pollen season were less likely to develop allergic rhinoconjunctivitis, IgE antibodies to pollen, or a positive screening test for IgE antibodies (odds ratio 0.28, 0.41, 0.35, respectively) than children born during the rest of the year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 24 publications
4
65
0
1
Order By: Relevance
“…We also found that sensitization to animal dander was more common among individuals born in January. Hwang et al [21] and Nilsson et al [22] have previously reported that the prevalence of immunoglobulin E antibodies to animal dander was higher in children born in autumn and winter. This may be, in part, explained by more frequent indoor contacts with animals during winters.…”
Section: Discussionmentioning
confidence: 97%
“…We also found that sensitization to animal dander was more common among individuals born in January. Hwang et al [21] and Nilsson et al [22] have previously reported that the prevalence of immunoglobulin E antibodies to animal dander was higher in children born in autumn and winter. This may be, in part, explained by more frequent indoor contacts with animals during winters.…”
Section: Discussionmentioning
confidence: 97%
“…Hidetoshi et al (1999) reported that the OR of an asthma diagnosis increased with eotaxin quartile, with the highest quartile having an OR of 5.4 compared with the lowest eotaxin quartile, and plasma eotaxin levels were associated with asthma, independent of age, race, sex, or smoking status. Previously, Nilsson et al (1997) observed that the season of birth was a significant predictor of atopic manifestations as well as circulating IgE antibodies to mixed allergens among children aged 15 or younger. Potential explanations for the differences by birth season include seasonal differences in pregnant mothers' exposure to seasonal allergens, the baby's exposure during susceptible periods after birth, or later environmental influences during the baby's development of immunity.…”
Section: Discussionmentioning
confidence: 98%
“…Birth during late winter and spring is associated with childhood asthma (Lendor et al, 2006). The prevalence of IgE antibodies to allergens is higher among children born in the autumn and winter seasons (Nilsson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The latter concept derives from a wide body of epidemiology demonstrating that exposure to relatively high levels of inhalant allergens during the first few months of life (exemplified by birth during the pollen season) is associated with markedly increased risk for expression of allergic respiratory disease in response to exposure to the same allergens in adult life (2,44), particularly in infants with positive atopic family history (45). These findings are not universally accepted, as some studies suggest that the highest risk is associated with birth 2 to 3 months before the peak of the pollen season (46), whereas others have failed to detect such relationships (47). However, it has been argued that these contrasting findings may be due to variations in the degree of fluctuation in aeroallergen levels throughout the year in different geographical areas.…”
Section: The Sensitization Window During Infancymentioning
confidence: 99%